Hubungan Pengetahuan dengan Kecemasan Menjelang Persalinan pada Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Tambang - Hafiza , Nur; Lubis, Duma Sari; Parmin, Joria (Evidence Midwifery Journal, 2022)
Anxiety is one of the causes of prolonged labor and fetal death. This study aims to determine the relationship between knowledge and anxiety in dealing with the period leading up to delivery in third trimester pregnant women in the work area of ??UPT BLUD Puskesmas Tambang in 2021. This type of research is quantitative analytical research. The study was conducted on 14-26 July 2021 with a total sample of 70 pregnant women in the third trimester using total sampling. Mother's knowledge data collection, while anxiety using a questionnaire. Analysis using univariate and bivariate Chi-Squre The results of the univariate analysis were 42 respondents (60.0%) who had poor knowledge while 29 respondents (41.4%) had good knowledge. The results showed that there was a relationship between knowledge (p value = 0.000) and the anxiety of pregnant women in the third trimester. The conclusion is that there is a relationship between knowledge and anxiety in the face of the pre-delivery period in trimester pregnant women. It is hoped that the results of this study will become input for the work area of ??the UPT BLUD Puskesmas Tambang to provide information to pregnant women to reduce maternal anxiety in facing childbirth.